Kualitas hidup dengan kualitas tidur remaja SMA Katolik Rex Mundi Manado di masa pandemi COVID-19 - Rahmat Aridi; Henry M. F. Palandeng; Ronald I. Ottay; Olivia Waworuntu (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2022)
Background: Adolescent is a period of growth that is most unique since there are very large changes covering physical, psychological and social development. The growth and development of adolescents are influenced by the quality of life with physical activity. However, the COVID-19 epidemic has severely limited the physical activity of adolescents, which has an impact on their quality of life and growth.Objective: The general aim of this study was to discover the quality of adolescent life and physical activity during the pandemic and the specific objective was to find out an overview of the quality of life, physical dimensions, psychological dimensions, social dimensions, environmental dimensions in physical activity.Method: This study used descriptive research with a cross-sectional design and it also used the cluster random sampling technique and simple random sampling by distributing WHOQOL-BREF questionnaires and the Global School-based Student Health Survey (GSHS) through google form.Results: Based on the 91 samples, it indicated that the physical health dimension of students with light physical activity, most of the good quality of life was 37.4, the psychological dimension with moderate physical activity, most of the good quality of life was 29.7, the social dimension with the most moderate student activity was 31.9.Conclusion: Students of SMP Negeri 2 Manado had a good and moderate quality of life, while their physical activity was moderate in all dimensions.Keywords: quality of life, physical activity, adolescents, COVID-19.Â